A potential food biopreservative, CecXJ-37N, non-covalently intercalates into the nucleotides of bacterial genomic DNA beyond membrane attack - Liu, Dongliang; Liu, Jun; Li, Jinyao; Xia, Lijie; Yang, Jianhua; Sun, Surong; Ma, Ji; Zhang, Fuchun (Food chemistry, 2017)
•CecXJ-37N shows small MICs (0.25–7.8μM) against 8 food-borne pathogenic strains.•CecXJ-37N shows low hemolysis and no cytotoxicity to normal mammalian cells.•CecXJ-37N induces pore-forming on E. coli cell membrane and causes cytolysis.•CecXJ-37N penetrates bacterial cell membrane and interacts with genomic DNA.•CecXJ-37N intercalates into nucleotides rather than binds to DNA backbone. The antibacterial activities and mechanism of an amide-modified peptide CecXJ-37N were investigated in this study. CecXJ-37N showed small MICs (0.25–7.8μM) against eight harmful strains common in food industry. The α-helix proportion of CecXJ-37N increased by 11-fold in prokaryotic membrane comparable environments; cytotoxicity studies demonstrated the MHC was significantly higher than that of non-amidated isoform. Moreover, CecXJ-37N possessed stronger capacities to resist trypsin and pepsin hydrolysis within two hours. Flow cytometry and scanning electron microscopy demonstrated that CecXJ-37N induced pore-formation, morphological changes, and lysed E. coli cells. Fluorescence microscopy indicated that CecXJ-37N penetrated E. coli membrane and accumulated in cytoplasm. Further ultraviolet–visible spectroscopy suggested that CecXJ-37N changed the action mode of parental peptide interacting with bacterial genome from outside binding to a tightly non-covalent intercalation into nucleotides. Overall, this study suggested that amide-modification enhanced antimicrobial activity and reduced the cytotoxicity, thus could be potential strategies for developing novel food preservatives.